2022
DOI: 10.3389/fpsyg.2022.998482
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the couriers’ experiences of logistics platform: The extension of expectation confirmation model and technology acceptance model

Abstract: The current study integrated the Extended Technology Acceptance Model (TAM) and included information system quality (ISQ), user interface (UI), knowledge sharing motivation (KSM), the expectation confirmation model (ECM), safety management practices (SMP), interface aesthetics (IA), and perceived value (PV) to evaluate the logistics couriers’ experience while using an Online logistics platform. This research examines the relationships of KSM, SMP, and ISQ on the TAM’s, perceived usefulness (PU), and perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 134 publications
0
2
0
Order By: Relevance
“…Many studies on information systems’ continuation intention have demonstrated the applicability of the ECM [ 33 , 34 , 35 , 36 ]. In this model, satisfaction significantly influences users’ intention to continue using a product or service.…”
Section: Research Modelingmentioning
confidence: 99%
“…Many studies on information systems’ continuation intention have demonstrated the applicability of the ECM [ 33 , 34 , 35 , 36 ]. In this model, satisfaction significantly influences users’ intention to continue using a product or service.…”
Section: Research Modelingmentioning
confidence: 99%
“…Al-Rahmi et al (2019) extended TAM with Innovation Diffusion Theory (IDT) to study students' intention to use e-learning systems. In addition, expectation-confirmation model (ECM) was combined with TAM by previous research to study users' continuance intention to use an online logistics platform (Zheng et al, 2022) and e-health services (Kumar & Natarajan, 2020). It was also demonstrated that Theory of Planned Behavior (TPB) could be successfully integrated with TAM (AlHamad, 2020;Nguyen et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%